Immigrant Job Search in the UK: Evidence from Panel Data - Paul Frijters; Michael A. Shields; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 2003)
Most immigrant groups experience higher rates of unemployment than the host countries native population, but it is as yet unclear whether differences in job search behaviour, or its success, can help explain this gap. In this paper, we investigate how the job search methods of unemployed immigrants compare with those of the native born, using panel data from the UK Quarterly Labour Force Survey. We explore the relative effectiveness of different job search methods, between the main native born and immigrant groups, in terms of their impact on the duration of unemployment. Our main finding is that immigrant job search in the UK is less successful than that of UK born whites. However their relative failure to exit unemployment cannot generally be explained by differences in the choice of main job search method or in observable characteristics. We find no support for a policy that would constrain immigrants to use verifiable job search methods.
Keywords: J61; J64; 330; unemployment; job search; immigrants; duration analysis; panel data; Migranten; Ausländische Arbeitskräfte; Arbeitsuche; Erfolgsfaktor; Schätzung; Dauer; Großbritannien